2014
DOI: 10.1007/s40471-014-0015-3
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Cancer: Priorities for Prevention

Abstract: Making a sizeable contribution to worldwide cancer mortality, adenocarcinomas and squamous cell carcinomas of the esophagus appear to be caused largely by environmental factors. Descriptive epidemiologic analyses demonstrate that these cancers occur at markedly different rates in populations around the world. Moreover, their incidences have changed greatly over time, strongly suggesting that their causes are modifiable. For adenocarcinomas, the risk factors identified consistently in analytic studies include g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 106 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…EAC is more common in developed countries, while ESCC highly occurs in developing countries; also, the third type is called small cell carcinoma, which is very rare. 20,21 Regarding the stages, it should be noted that the first stage is the primary tumor, the second stage is lymph node involvement, and the third stage is metastasis. 22 EC cancer has no symptoms in the early stages and usually shows symptoms over the age of 50; in other words, the disease has no symptoms until metastasis, so that the death rate is high.…”
Section: Esophageal Cancer Classificationmentioning
confidence: 99%
“…EAC is more common in developed countries, while ESCC highly occurs in developing countries; also, the third type is called small cell carcinoma, which is very rare. 20,21 Regarding the stages, it should be noted that the first stage is the primary tumor, the second stage is lymph node involvement, and the third stage is metastasis. 22 EC cancer has no symptoms in the early stages and usually shows symptoms over the age of 50; in other words, the disease has no symptoms until metastasis, so that the death rate is high.…”
Section: Esophageal Cancer Classificationmentioning
confidence: 99%
“…The incidence of esophageal cancer is the seventh in the world, and the mortality rate is the sixth 1 , 2 . Studies have shown that the 5-year survival rate of advanced esophageal cancer is only 18%, while the 5-year survival rate of early esophageal cancer is more than 95%, so the early diagnosis of esophageal cancer has important clinical significance 3 , 4 . At present, the examination of esophageal cancer is usually performed through direct observation of gastroscopy and then biopsy to confirm the tumor stage.…”
Section: Introductionmentioning
confidence: 99%
“…Earlystage EC is not very lethal; its five-year survival rate is over 95%. However, if EC lesions are diagnosed in advanced stages, a poor prognosis may become inevitable; at this stage, the five-year survival rate drops to only 5% [2], [3]. Therefore, diagnoses of EC in the early stage are of great significance in the clinic.…”
Section: Introductionmentioning
confidence: 99%